2022
DOI: 10.1002/ags3.12601
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and surgical outcomes in gastrointestinal cancer: Integration of geriatric assessment and prehabilitation into surgical practice for vulnerable patients

Abstract: As life expectancy increases, the older population continues to grow rapidly, resulting in increased requirement for surgery for older patients with gastrointestinal cancer. Older individuals represent a heterogeneous group in terms of physiological reserves, co‐morbidity, cognitive impairment, and disability. Owing to the lack of treatment guidelines for vulnerable patients with gastrointestinal cancer, these patients are more likely to be at risk of undertreatment or overtreatment. Hence, the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Prehabilitation may be effective for patients with a poor physical function, nutritional status, or cognitive function. Prehabilitation is a preoperative multidisciplinary intervention that includes exercise and nutritional support 29 . Mima et al reported that preoperative rehabilitation and nutritional intervention improve surgical outcomes and reduce the incidence of postoperative complications in gastroenterological surgery 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prehabilitation may be effective for patients with a poor physical function, nutritional status, or cognitive function. Prehabilitation is a preoperative multidisciplinary intervention that includes exercise and nutritional support 29 . Mima et al reported that preoperative rehabilitation and nutritional intervention improve surgical outcomes and reduce the incidence of postoperative complications in gastroenterological surgery 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Prehabilitation is a preoperative multidisciplinary intervention that includes exercise and nutritional support 29 . Mima et al reported that preoperative rehabilitation and nutritional intervention improve surgical outcomes and reduce the incidence of postoperative complications in gastroenterological surgery 29 . Therefore, the prehabilitation of vulnerable patients may reduce the incidence of postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and severity of these established conditions at diagnosis can help to identify patients at the highest risk of experiencing poor surgical outcomes, and, therefore, those who are likely to benefit most from prehabilitation. For instance, patients who are frail are more likely to benefit from prehabilitation given the association of frailty with post-operative complications [55,78]. Thus, assessing risk factors and metrics of frailty and physical function before cancer treatments and operations becomes essential in informing the components of prehabilitation and supporting overall survival [8,72,75].…”
Section: Additional Considerations Of Prehabilitation In Hpb Cancer P...mentioning
confidence: 99%
“…With the rapid aging of populations worldwide, the number of vulnerable patients with cancer has increased [5][6][7]. Accumulating evidence indicates that vulnerable patients with gastrointestinal cancer are more likely to have worse surgical outcomes or poor prognosis [8][9][10]. Hence, identifying and improving perioperative vulnerability or frailty may provide favorable clinical outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%